Boron Nanosheets for Efficient All‐Optical Modulation and Logic Operation. Issue 13 (6th May 2019) - Guo, Qiangbing; Wu, Kan; Shao, Zhengpeng; Basore, Endale T.; Jiang, Peng; Qiu, Jianrong
Abstract: Due to its unique trivalent electronic configuration, boron features richer properties as well as higher chemical and structural complexities compared with its right neighbor carbon. Consequently, over a decade later than the exfoliation of graphene, borophene has just been experimentally demonstrated on certain metal substrates and under ultrahigh‐vacuum conditions, which, however, limit its wide and in‐depth experimental researches. Here, for the first time, by employing liquid‐exfoliated boron nanosheets, all‐optical signal processing application is explored based on its superior photo‐thermal response. A stable all‐optical modulator is presented, which shows significantly faster response speed and higher modulation efficiency compared with other 2D materials‐based similar devices. Furthermore, boron nanosheets‐based all‐optical logic gating operations are also demonstrated. This work not only presents an excellent 2D material‐based all‐optical signal processing device, but also marks a significant step toward optical and photonic researches as well as device applications of 2D boron. Abstract : Boron nanosheets‐based all‐optical modulation and logic operations are experimentally demonstrated by exploiting the superior photo‐thermal response in liquid‐exfoliated boron nanosheets, which, surprisingly, show an order of magnitude faster response speed and higher modulation efficiency compared with other 2D materials‐based (including graphene, transition metal dichalcogenide, black phosphorus) similar devices.